Electromagnetic (EM) propagation through iron (III) oxide-based building materials embedded with electrically small antennas at microwave frequencies (part 1) - Sheng, Lin (Nanyang Technological University, 2023)
Concrete is the most widely used material across the world for construction of buildings and other facilities due to its inexpensiveness, durability, and ease of use. However, with the development and popularity of 5G cellular network in the recent years, concrete buildings have become a huge obstacle for the small wavelength of 5G by dissipating or reflecting much of the signal's energy (Attenuation). Many prior research have been done to find a way to subside this effect but most focused on 4G network. This project found out that by embedding electrically small antenna (ESA) and adding Iron(III) Oxide worth 2% of the total weight of the concrete can significant reduce the attenuation experienced by a 5G 3.5GHz electromagnetic signal. Moreover, it was also found that embedding ESA inside concrete will result in the increase of resonant frequency over time as the concrete cures.